Exploration of Intellectual Themes in Brahui Fictional Narratives (Novels) - Rakhshani, Muhammad Akram; Ali, Liaquat (sourcecoder, 2024)
The emergence of Brahui fiction in the form of novels marks a significant milestone in the literary history of the Brahui language, with its genesis dating back to 1989. Over the past few decades, approximately two dozen novels have been published, representing a rich tapestry of intellectual and cultural discourses. This study critically explores the intellectual themes embedded in Brahui fictional narratives, with a particular focus on the portrayal of women's issues and perspectives. A predominant characteristic of Brahui novels is their engagement with the multifaceted experiences of women, reflecting broader societal, cultural, and psychological dimensions. Themes such as gender roles, women's empowerment, social justice, and the challenges of traditional norms frequently resonate throughout these narratives, providing a nuanced lens into the lived realities of women in Brahui society. By employing literary analysis and thematic categorization, this paper aims to illuminate the intellectual depth and cultural significance of these works. This exploration not only sheds light on the thematic richness of Brahui novels but also underscores their role as a medium for intellectual dialogue and social transformation.